The Egyptian food subsidy system: structure, performance, and options for reform - Ahmed, Akhter; Gutner, Tamar; Lofgren, Hans; Bouis, Howarth E. (International Food Policy Research Institute, 2001)
Egypt's food subsidy system has been a mainstay of the government's long-term policy of promoting social equity and political stability. It has also been a major component of the social safety net for the poor, guaranteeing the availability of affordable staples, helping to reduce infant mortality and malnutrition, and mitigating the adverse effects of recent economic reform and structural adjustment.The cost of the system has declined considerably from 14 percent of government expenditures in 1980/81 to 5.6 percent in 1996/97. The absolute cost, however, remains high: In 1996/97,the total cost was 3.74 billion Egyptian pounds (LE)or about US$1.1 billion.The government and various stakeholders agree that the system's costs can be further reduced and its efficiency improved with better targeting to the needy. The Egyptian Food Subsidy System: Structure, Performance, and Options for Reform evaluates the economic, political, and technical feasibility of reducing costs while improving or maintaining the welfare of the poor.The report addresses five questions: (1)How well does the present system target the poor? (2)How much leakage "of the pilferage of subsidized foods in the distribution channel”occurs? (3)At what cost does the government transfer income to the needy? (4)How can subsidies be better targeted to the needy?and (5)What are politically feasible options for reform?